Visual search strategies in soccer players executing a power vs. placement penalty kick - Timmis, M.; Turner, K.; Van Paridon, K. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: The visual search strategies employed by soccer players when executing the penalty kick has received widespread research interest. Consistent differences have been highlighted in visual search strategies between elite and sub elite soccer players and the strategies adopted between penalty kickers. When taking a soccer penalty kick, players can execute either a placement or power shot. To date, there is no research investigating the visual search strategies of soccer players when executing a power or placement penalty kick. This was the focus of the present study. Methods: 12 amateur footballers took 2 power and placement penalty kicks, indoors, according to The Football Association (F.A.) guidelines for indoor football. A goalkeeper stood in the centre of a goal measuring 3.66m wide by 1.83m high. A football was placed 6 metres from the centre of the goal. The power penalty required players to kick the football with maximum power whilst ensuring a goal was scored. The placement penalty required players to kick the football accurately to a corner of the goal. Eye movements of the penalty kicker were recorded using SMI Eye tracking glasses. Peak horizontal velocity of the football when being kicked and end location of the football were also recorded. Results: The football was kicked significantly harder and more centrally in the power compared to the placement penalty (p<.001 and p=.018 respectively). In the power penalty, the relative fixation length was significantly longer on the ball (p=.049) and goalkeeper (p=.042), but shorter on the goal (p=.037) compared to the placement penalty. There were significantly more fixations on the goalkeeper (p=.036) but less on the goal (p=.044) in the power compared to placement penalty. Average fixation length was significantly shorter on the goal in the power compared to placement shot (p=.011). There was no significant difference in total trial length between conditions or in the number of penalties scored (p>.05). Discussion/conclusion: Results highlight differences in visual search strategies when executing placement and power penalty kicks. Players in the power shot fixated and kicked more centrally to the goal. In the placement shot, fixations and kicks were directed more towards the periphery of the goal. These findings add further support to the tight coupling between gaze and visuomotor control of aiming, and the importance of the visual system in guiding output from the motor system (Land, 2009; Wood and Wilson, 2010).